Prosthetic Aortic Valves: Challenges and Solutions - Musumeci, Lucia; Jacques, Nicolas; Hego, Alexandre; Nchimi, Alain; Lancellotti, Patrizio; Oury, Cécile (Frontiers in Cardiovascular Medicine, 2018)
Aortic Valve Disease (AVD) is the most common Valvular Heart Disease (VHD), affecting millions of people worldwide. Severe AVD is treated in most cases with prosthetic aortic valve replacement, which involves the substitution of the native aortic valve with a prosthetic one. In this review we will discuss the different types of prosthetic aortic valves available for implantation and the challenges faced by patients, medical doctors, researchers and manufacturers, as well as the approaches that are taken to overcome them.